2017
DOI: 10.1111/obes.12180
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing the Last Drop Out of Your Suppliers: An Empirical Study of Market‐Based Purchasing Policies for Generic Pharmaceuticals

Abstract: We study the effect of the degree of exclusivity for the lowest bidder on the average price of generic pharmaceuticals in the short and long terms. Our results indicate that a 1-percentage-point gain in market share of the lowest bidder reduces average costs by 0.2% in the short term and 0.8% in the long term, but also reduces the number of firms by 1%. We find that reducing the number of firms has a strong positive (and hence counteracting) effect on average prices, a 1% reduction raising prices by approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Medicine prices in the private sectors were consistently higher than tender prices. This was similar to findings in other studies that proved tender medicine prices showed an overall decrease in medicine price [ (Baldi & Vannoni, 2015); (Bartels, 2016); (Bergman, et al, 2017); (Curto, et al, 2014); (Danzon, et al, 2015); (Kanavos, et al, 2009); (Petrou & Talias, 2014); (Raventos & Zolezzi, 2015) and ]. The most probable reason for this difference is the methodology adopted for the tendering process in the public sector.…”
Section: Discussionsupporting
confidence: 90%
“…Medicine prices in the private sectors were consistently higher than tender prices. This was similar to findings in other studies that proved tender medicine prices showed an overall decrease in medicine price [ (Baldi & Vannoni, 2015); (Bartels, 2016); (Bergman, et al, 2017); (Curto, et al, 2014); (Danzon, et al, 2015); (Kanavos, et al, 2009); (Petrou & Talias, 2014); (Raventos & Zolezzi, 2015) and ]. The most probable reason for this difference is the methodology adopted for the tendering process in the public sector.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, this paper contributes by studying the effects on individual prices and by doing this separately for generics and originals. Unlike Bergman, Granlund and Rudholm (2017), who implicitly assumed firms to have naïve expectations about the number of competitors, we also allow for rational expectations and find evidence consistent with this.…”
Section: Introductionmentioning
confidence: 73%
“…reduce the administrative fees in order to increase the number of active firms in small exchange groups. This paper relates to Bergman, Granlund and Rudholm (2017) which used part of the data used in this study to investigate how changing the market share for the lowest bidder affects the cost per defined dose.…”
Section: Introductionmentioning
confidence: 99%
“…This paper relates to Bergman et al (2017) and Granlund and Bergman (2018)both of which used dynamic models to study competition effects. However, these papers studied prices for off-patent pharmaceuticals and focused on the effects of competition from generic substitutes.…”
Section: Introductionmentioning
confidence: 99%